Seasonal Shifts in Bacterial and Fungal Microbiomes of Leaves and Associated Leaf-Mining Larvae Reveal Persistence of Core Taxa Regardless of Diet - Šigutová, Hana; Šigut, Martin; Pyszko, Petr; Kostovčík, Martin; Kolařík, Miroslav; Drozd, Pavel (Microbiology spectrum, 2023)
Microorganisms are key mediators of interactions between insect herbivores and their host plants. Despite a substantial interest in studying various aspects of these interactions, temporal variations in microbiomes of woody plants and their consumers remain understudied. In this study, we investigated shifts in the microbiomes of leaf-mining larvae (Insecta: Lepidoptera) and their host trees over one growing season in a deciduous temperate forest. We used 16S and ITS2 rRNA gene metabarcoding to profile the bacterial and fungal microbiomes of leaves and larvae. We found pronounced shifts in the leaf and larval microbiota composition and richness as the season progressed, and bacteria and fungi showed consistent patterns. The quantitative similarity between leaf and larval microbiota was very low for bacteria (~9%) and decreased throughout the season, whereas fungal similarity increased and was relatively high (~27%). In both leaves and larvae, seasonality, along with host taxonomy, was the most important factor shaping microbial communities. We identified frequently occurring microbial taxa with significant seasonal trends, including those more prevalent in larvae (Streptococcus, Candida sake, Debaryomyces prosopidis, and Neoascochyta europaea), more prevalent in leaves (Erwinia, Seimatosporium quercinum, Curvibasidium cygneicollum, Curtobacterium, Ceramothyrium carniolicum, and Mycosphaerelloides madeirae), and frequent in both leaves and larvae (bacterial strain P3OB-42, Methylobacterium/Methylorubrum, Bacillus, Acinetobacter, Cutibacterium, and Botrytis cinerea). Our results highlight the importance of considering seasonality when studying the interactions between plants, herbivorous insects, and their respective microbiomes, and illustrate a range of microbial taxa persistent in larvae, regardless of their occurrence in the diet. IMPORTANCE Leaf miners are endophagous insect herbivores that feed on plant tissues and develop and live enclosed between the epidermis layers of a single leaf for their entire life cycle. Such close association is a precondition for the evolution of more intimate host-microbe relationships than those found in free-feeding herbivores. Simultaneous comparison of bacterial and fungal microbiomes of leaves and their tightly linked consumers over time represents an interesting study system that could fundamentally contribute to the ongoing debate on the microbial residence of insect gut. Furthermore, leaf miners are ideal model organisms for interpreting the ecological and evolutionary roles of microbiota in host plant specialization. In this study, the larvae harbored specific microbial communities consisting of core microbiome members. Observed patterns suggest that microbes, especially bacteria, may play more important roles in the caterpillar holobiont than generally presumed.
Keywords: dieta; mykobiom; Seasons; bacteria; Mycobiome; invertebrate-microbe interactions; zvířata; plant-microbe interactions; fungi; larva; Animals; microbial ecology; Diet; Larva; Bacteria; microbial communities; roční období